2022
DOI: 10.1101/2022.09.30.510198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imaging crossing fibers in mouse, pig, monkey, and human brain using small-angle X-ray scattering

Abstract: Myelinated axons (nerve fibers) efficiently transmit signals throughout the brain via action potentials. Multiple methods that are sensitive to axon orientations, from microscopy to magnetic resonance imaging, aim to reconstruct the brain's structural connectome. As billions of nerve fibers traverse the brain with various possible geometries at each point, resolving fiber crossings is necessary to generate accurate structural connectivity maps. However, doing so with specificity is a challenging task because s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Given its independence from myelin birefringence, ComSLI can yield neuropathologic insights when combined with myelin-sensitive microscopic methods such as 3D-PLI [18][19][20] . polarizationsensitive optical coherence tomography 16,17 , and X-ray scattering 9,10,36,37 . Especially compared to 3D-PLI, which is the method-of-choice for micron-resolution fiber mapping on sections, ComSLI can be applied to virtually any section independent of sample preparation or birefringence, including FFPE sections, and can resolve crossing fibers per pixel, with an easyto-implement and cost-effective setup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given its independence from myelin birefringence, ComSLI can yield neuropathologic insights when combined with myelin-sensitive microscopic methods such as 3D-PLI [18][19][20] . polarizationsensitive optical coherence tomography 16,17 , and X-ray scattering 9,10,36,37 . Especially compared to 3D-PLI, which is the method-of-choice for micron-resolution fiber mapping on sections, ComSLI can be applied to virtually any section independent of sample preparation or birefringence, including FFPE sections, and can resolve crossing fibers per pixel, with an easyto-implement and cost-effective setup.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy resolves nerve cells at nanometer resolution 5,6 , but tracking the fiber pathways is limited to small tissue volumes 7,8 . Small-angle X-ray scattering (SAXS) can directly probe multi-directional fiber pathways 9,10 , but cannot provide whole-brain micrometer resolution and requires expensive equipment such as synchrotrons. Various light microscopy techniques visualize nerve fibers at high resolution and over larger fields of view, using staining 11,12 , fluorescence 13 , or other contrast mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method can be tomographic (SAXS tensor tomography – Liebi et al, 2015 ; Gao et al, 2019; Georgiadis et al, 2021 ), and 3D-scanning SAXS (3D-sSAXS) can provide 3D distributions of axon orientations in tissue sections ( Georgiadis et al, 2020 ). Recent studies further revealed that SAXS can exploit the modulations in the azimuthal position of the myelin-specific Bragg peaks to resolve crossing nerve fiber populations across species ( Georgiadis et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%